Methods of Organizing the Teaching Activity in Multi-Grade Classes - Dana Jucan (Babes-Bolyai University, 2023)
In multi-grade classes, there are different versions of each type of lesson depending on the school subject, the manner of integrating the lesson contents and the content's particularities, volume, and density, but also the age level of the students. From this point of view, the classification of lessons according to these criteria could be reconsidered as the teaching of the subjects is in a continuous dynamism marked by creativity and not by the usual rigors that would require different algorithms. This fact can also be supported by the integration within each lesson of recreational moments, lasting between five and fifteen minutes. Therefore, the stages of each lesson will be modified according to various factors related to the specifics of the activity in multi-grade education. The present study demonstrates how the organization and conduct of lessons differ from one case to another depending on the types of lessons that are combined; it also shows that, for the judicious distribution of time, it is necessary to carefully study the content of the lessons and compare the materials provided for each class. Less time can be allocated to direct activity in the younger class if the students are familiarized with certain concepts throughout previous lessons, which they can then deepen or expand through independent activity, while in the older class the material is entirely new and requires more in-depth explanation.